Penerapan sumur bor sistem pipa imbuh untuk keperluan air bersih - Rahmansah Rahmansah; Bakhrani Rauf; Muhammad Ardi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The problems faced by partner in TellulimpoeVillage and Patampanua Village were: (1) people in that areasdo not have the knowledge about the drill pipe of the rechargesystem which can be used as a source of clean water; (2) theydo not have the skills to drill a drill pipe system; (3) they donot have the skills to install drill well pipes and exhaust pipes;and (4) they do not have the skills to install water pumpmachines and supply pipes. The solutions to solving partnerproblems were: (1) design a borehole pipe system; (2) providea drill pipe system; (3) provide borehole material for anextension pipe system; and (4) train the partner to make drillwells for pipe systems (drilling, installing pipes and installingmachinery and supply pipes). The methods used included: (1)lectures; (2) demonstrations; (3) discussion; (4) question andanswer; and (5) accompanying partners to make a boreholepipe system. The results achieved were: (1) partners haveknowledge of the wellbore of an extension pipe system thatcan be used to pump groundwater; (2) partners have the skillsto drill a borehole system for the pipe system; (3) partnershave the skills to install drill well pipes and recharge pipes;and (4) partners have the skills to install water pump machinesand supply pipes.